Congenital heart disease in children with Down syndrome in Afghanistan - Abdul Muhib Sharifi; Abdul Rashid Mansoor; M. Akbar Ibrahimi; Abdul Wali; Wali Wali; Khesrow Ekram (Paediatrica Indonesiana, 2018)
Background Congenital heart disease (CHD) is frequently cited as the main cause of death in the pediatric Down syndrome (DS) population. The prevalence and spectrum of CHD patterns in DS varies widely worldwide; this variation could be due to sociodemographic, genetic, and/or geographic factors. Objective To verify the prevalence, pattern, and frequency distribution of CHD in children with Down syndrome. Methods A three-year retrospective study was conducted in children aged 0-14 years with Down syndrome who underwent echocardiography for possible CHD from January 2014 to December 2016, based on the Pediatric Unit CHD Registry of the Cardiac Research Institute, Kabul Medical University. Clinical, echocardiographic, and outcome data were collected and sorted according to confirmation of the syndrome and echocardiography result. Results During the three-year study period, 420 DS patients were identified, 286 (68%) of whom had CHDs. The prevalence of isolated and multiple CHD in the 420 children with DS were 38% (160 patients) and 30% (126 patients), respectively. Ventricular septal defect (23%) and atrial septal defect (16.4%) were the most common isolated defects. The combination of VSD and ASD (19.9%) were the most frequent multiple CHDs. The most common associations of CHD were VSD + ASD (19.9%) and VSD + PDA (9%). Conclusion A high prevalence of CHDs was noted in children with Down syndrome. VSD and ASD are the most commonly diagnosed isolated CHDs in our study. ASD + VSD is the most common multiple CHD pairing. To our knowledge, this is the first extensive study in Afghanistan to demonstrate the pattern and prevalence of CHD associated with Down syndrome.